Modelling windage power loss from an enclosed spur gear - Eastwick, Carol; Simmons, K.; Al-Shibl, K. (SAGE, 2007)
Within a gearbox the majority of transmission losses can be attributed to bearing losses, meshing losses, or losses due to windage/churning. In this paper the commercial computational fluid dynamics (CFD) code Fluent 6.2.16 is applied in a two-dimensional study of windage power loss (WPL) from a single spur gear rotating in air. By comparing CFD data to published experimental data appropriate grid density and modelling parameters are identified. The model is used to investigate how peripheral shrouding affects WPL and whether WPL can be reduced through minor modifications to tooth tip geometry. Non-dimensional shroud spacings (ratio of gap to gear PCD) of between 0.005 and 0.05 were investigated at shaft speeds between 5000 and 20 000 r/min. Although CFD data compared reasonably well to experimental data, trends were not reproduced and an optimum shroud could not be identified. A full three-dimensional study is recommended. Modifying the tooth tip by adding a small chamfer on the leading edge reduced WPL by ~6 per cent. A small fillet increased total WPL by a similar amount suggesting that WPL may increase as a gear wears. This preliminary study suggests further work in this area would be beneficial.